Review on bubble formation, rise and break-up in a gas-liquid system - Kulkarni, Amol A.; Joshi, Jyeshtharaj B. (Industrial & Engineering Chemistry Research, 2005)
The formation of gas bubbles and their subsequent rise due to buoyancy are very important fundamental phenomena that contribute significantly to the hydrodynamics in gas−liquid reactors. The rise of a bubble in dispersion can be associated with possible coalescence and dispersion followed by its disengagement from the system. The phenomenon of bubble formation decides the primitive bubble size in the system (which latter attains an equilibrium size), whereas the rise velocity decides the characteristic contact time between the phases which governs the interfacial transport phenomena as well as mixing. In view of their importance, we herein present a comprehensive review of bubble formation and bubble rise velocity in gas−liquid systems. The emphasis of this review is to illustrate the present status of the subjects under consideration and to highlight the possible future directions for further understanding of the subject. The bubble formation at a single submerged orifice and on multipoint sieve trays in Newtonian as well as non-Newtonian stagnant and flowing liquids is discussed in detail, which includes its mechanism as well as the effect of several system and operating parameters on the bubble size. The comparison of results has shown that the formulation of Gaddis and Vogelpohl22 is the most suitable for the estimation of bubble size in stagnant liquids. The special cases, such as bubble formation in reduced gravity conditions and weeping and in flowing liquids, are discussed in detail. The section on the rise of a gas bubble in liquid covers the various parameters governing bubble rise and their effect on the rise velocity. A comprehensive comparison of the various formulations is made by validating the predictions with experimental data for Newtonian as well as non-Newtonian liquids, published over last several decades. The results highlight that for the estimation of rise velocity in (i) pure Newtonian liquids, (ii) contaminated Newtonian liquids, and (iii) non-Newtonian liquids, the formulation based on the wave theory by Mendelson,190 Nguyen's formulation,155 and the formulation by Rodrigues,153 (last two, based on the dimensional analysis), respectively are the most suitable. The motion of bubbles in non-Newtonian liquids and the reason behind the discontinuity in the velocity are also discussed in detail. The bubble rise is also analyzed in terms of the drag coefficient for different system parameters and bubble sizes.

Reaction engineering for continuous production of silver nanoparticles - Deshpande, Javdeep B.; Kulkarni, Amol A. (Chemical Engineering & Technology, 2018)
A scalable process for the production of silver nanoparticles that allows for complete conversion of the limiting reactant is analyzed in detail. The kinetics of silver nanoparticle synthesis using citrate reduction are investigated and used for development of a reaction engineering model to facilitate the reactor design. The effect of temperature, pH, concentration and mixing (axial dispersion) on the rates of nucleation and growth are analyzed quantitatively. An approach that considers reaction kinetics coupled with quality of dispersion is developed for reactor design as well as selection of reactor configurations for the synthesis of specific particle sizes. The developed approach has been applied for continuous production of 10-L suspension silver nanoparticles with very narrow particle size distribution.
Keywords: kinetics; particle size distribution; rate constant; Reactor design; Silver nanoparticle production

Residence time distribution of powders in a vertical single screw reactor: experiments using salt-coated tracer particles and simulations - Rajendra, R. Sriram; Palgadhmal, Anil V.; Kulkarni, Amol A. (Particuology, 2025)
The use of single and twin-screw extruders for solid-phase reactions is a promising method to intensify a process in a more sustainable manner. In this manuscript, we report a detailed analysis of the residence time distribution (RTD) in vertical single-screw reactors. The results will help in the selection of the right screw design that would help achieve the desired residence time, which is necessary for a reaction to happen. Experiments were conducted in three vertical screw reactors (having fixed shaft diameter) with varying dimensions using granular free-flowing powders of sodium chloride and silica with a mean particle size of similar to 25 mu m. RTD behavior was modeled using the radial particle velocities in the screw reactor's centrifugal field. Further, a method is proposed for estimating the axial dispersion coefficient of dry powders in such sheared flows using true and bulk densities of the powder and the screw shear rate. This dispersion coefficient is used in the axially dispersed plug flow model to describe the RTD behavior of screw reactors with acceptable accuracy. The theoretically predicted and experimentally obtained dispersion coefficients are found to be similar thereby confirming the suitability of the model. (c) 2025 Chinese Society of Particuology and Institute of Process Engineering, Chinese Academy of Sciences. Published by Elsevier B.V. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Bulk density; Centrifugal field in screw reactor; Particle inertial number; Powder dispersion coefficient; Powder flow; Single-screw extruder